2015
DOI: 10.1007/s10067-015-2960-8
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis in spondyloarthritis including psoriatic arthritis, ankylosing spondylitis, and inflammatory bowel disease

Abstract: Uveitis is a common complication of spondyloarthritis. The "phenotype" of the uveitis characteristic of ankylosing spondylitis (sudden onset, anterior, unilateral, recurrent, more often male) may differ from the phenotype often seen with either psoriatic arthritis or inflammatory bowel disease (insidious onset, anterior and intermediate, bilateral, chronic, and/or more often female). The frequency of uveitis is also much greater in association with ankylosing spondylitis than with either inflammatory bowel dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 27 publications
2
52
0
5
Order By: Relevance
“…36 Typical attacks are abrupt and unilateral, with intense circumlimbal hyperemia, pain, photophobia, and visual impairment. Subsequent attacks may involve the contralateral eye.…”
Section: Extra-articular Manifestationsmentioning
confidence: 99%
“…36 Typical attacks are abrupt and unilateral, with intense circumlimbal hyperemia, pain, photophobia, and visual impairment. Subsequent attacks may involve the contralateral eye.…”
Section: Extra-articular Manifestationsmentioning
confidence: 99%
“…In AS, the visual prognosis after acute AU is excellent with adequate treatment, which usually includes topical (and at times oral and locally injected) corticosteroids 4. Observational studies have suggested that sulfasalazine (SSZ) may prevent recurrence of AU in patients with AS5 6 and some positive data also exist for methotrexate (MTX)7 and non-steroidal anti-inflammatory drugs (NSAID) 8.…”
Section: Introductionmentioning
confidence: 99%
“…These associations are not surprising as comorbidities of some of these conditions are well recognised in the context of IBD 283285 and because almost all are associated with an increased incidence of similar pathologies such as arthritis 286 , uveitis 287, 288 and bowel inflammation 289292 .…”
Section: Identifying the Molecular Cause/s Of The CD Phenotypementioning
confidence: 99%